IT OUTSOURCING: METHODOLOGY FOR SELECTING SUPPLIERS CRITERION FOR COMPETITIVE ADVANTAGE - José Celso Contador (JISTEM: Journal of Information Systems and Technology Management, 2012)
The main reasons that motivate companies to outsource the services of Information Technology (IT) are: reducing costs, improving service quality and concentration on their core competencies. And the decision criteria of the contracting company are focused on those reasons. This article proposes a strategic criterion: the company should hire the supplier that best leverages their competitive advantages. This criterion implies the need to develop a specific methodology to this purpose, which is reported in this paper. To support it, the authors analyzed the models of Porter, Resource-Based View, Balanced Scorecard and the Fields and Weapons of the Competition, and making an option for the latter. The methodology was developed and applied to an Insurance Company and accepted by their leaders.